PEMBERIAN MOTIVASI DAN REWARD TERHADAP KINERJA RESSELER - Ahmad Yusdarwin Waworuntu (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2023)
The goal to be achieved from this research is to find out and analyze the extent to which motivation and rewards influence reseller performance through job satisfaction at a Makassar herbal company. The population of this study were herbal company resellers in Makassar with a total sample of 120 people who could be used as respondents. The analytical method used is Descriptive Statistics and Linear Regression Analysis. The results of this study explain that there is a positive and significant influence between motivation and reward variables on reseller performance.